MOMBAÇA GRASS PRODUCTIVITY (Panicum maximum), WITH DIFFERENT DOSES OF BIOFERTILIZER - Simonetti, A.; Marques, W. M.; Costa, L. V. C. (Revista Brasileira de Engenharia de Biossistemas, 2016)
This study aimed to verify the influence of the application of dairy cattle manure treated in biodigesters anaerobics, in the form of biofertilizer on the productivity of grass Mombaca, upland conditions. The work was conducted at the Institute of Biotechnology - IBIOTEC belonging to UNIARA, Araraquara – SP. To obtain the fertilizer was taken dilution of waste water and stored in a digester Indian model fiberglass with a useful capacity of 1000 L, installed in refer institute. The fertilizations were made to haul after each lowering of the plots. The design was a randomized complete block d with four treatments and four replications, with different doses of biofertilizers, as follows: 0; 50m³; 100m³ and 200m³ / ha. The variables were: height, per hectare production (dry matter and green matter), and chemical quality. They observed that the treatments that received the highest dose of biofertilizer, showed higher values for productivity Dry Matter, Green Matter and protein. It follows that the application of biofertilizers is beneficial to the pasture system, but their doses should be studied and their response in production can obtained the long run.